(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rahmah H, Wijayanto N, Wulandari AS. 2023. The growth of sengon (Parasarienthes falcataria) and citronella (Cymbopogon nardus) productivity performance in agroforestry system. Biodiversitas 24: 3114-3119. Sengon is a fast-growing plant species widely planted in community forests. Sengon is widely cultivated in agroforestry systems with seasonal crops. The main obstacle to cultivation in agroforestry systems is low growth due to competition for nutrients and low absorption of sunlight. This study aims to analyze the growth of sengon varieties and citronella varieties. The research was conducted for six months in the Cikabayan field, Faculty of Forestry, IPB University, Bogor, West Java. This study consisted of two activities: (i) analyzing the effect of the two-year-old sengon variety on the growth of tree height, diameter, crown, and volume, (ii) analyzing the effect of the citronella variety on the growth and yield of citronella oil. The experiment was designed with three factors, a completely randomized design with three replications. The results showed that Sengon Solomon had higher growth than Sengon Kendal. Sengon Solomon F2 had better growth than Sengon Solomon F1 and Kendal locale. Citronella plants grown under the local stands of Sengon Kendal had the best productivity. Lemongrass variety G1 had better growth than the Sitrona 2 Agribun variety in the shaded condition of sengon stands. However, the Sitrona 2 Agribun variety’s yield has a higher value than the G1 citronella variety.